Privacy Compliance in Software Development: A Guide to Implementing the LGPD Principles Extended Abstract – CTDSI/CTCCSI 2023 - Rocha, Lucas Dalle; Canedo, Edna Dias (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2023: Anais Estendidos do XIX Simpósio Brasileiro de Sistemas de Informação, 2023)
This study examines the need for compliance with Brazil’s General Data Protection Law (LGPD) as data breaches become more common with the widespread use of digital applications. The study identified obstacles to implementing LGPD principles and proposes a reference guide to assist ICT professionals. Surveying professionals from various software development fields, the study found that participants struggled with at least one LGPD principle, often due to a lack of knowledge about implementation techniques. Therefore, the proposed guide aims to improve developers’ understanding of techniques to ensure compliance with the LGPD.